Promoting Scientific Research: rNFT and DeSci Conjunction - Mikhaylov, Dmitry; Shafeeg, Abdulla; Shazhaev, Ilman; Tularov, Arbi (AI Society & STMIK Indonesia, 2024)
NFTs are non-fungible tokens. Like cryptocurrencies, they appeared as a result of the formation of the blockchain. True, unlike, say, Bitcoin, each NFT is unique and has its own value. If one conventional cryptocurrency unit does not differ in any way from another similar one (for example, one Ethereum does not differ in any way from another and is completely interchangeable without loss of value), then the situation is different with NFT. Tokens are used to secure rights to a unique object, such as a digitized work of art or artifacts in video games. Tokens are stored in the blockchain and contain the address of the object. To store the metadata and media to which the tokens are assigned, the InterPlanetary File System (IPFS) file system distributed over many computers is most often used. Farcana has suggested applying the same principle to scientific research. By introducing the MetaDeSci, Farcana has created a space where the gamers, gaming platforms, investors, scientists and universities are capable of using the rNFT to finance research, share data and promote science altogether, maintaining transparency.